2022
DOI: 10.3389/fpls.2022.939299
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of the Transcriptome and Metabolome Revealed the Mechanism of Petal Coloration in Bauhinia variegata

Abstract: Bauhinia variegata petals are colorful, rich in anthocyanins, and have ornamental, nutritional, and medicinal value. However, the regulatory mechanism of anthocyanin accumulation in B. variegata remains unclear. In this study, a combined analysis of the metabolome and transcriptome was performed in red and white B. variegata cultivars in the early, middle, and blooming stages. A total of 46 different anthocyanins were identified, of which 27 showed marked differences in accumulation between the two cultivars, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
3
3
0
Order By: Relevance
“…In the present study, the expression levels of genes encoding DFR (LOC101293459 and LOC101293749) were higher in BF1 and BF2 than in FN, resulting in the accumulation of anthocyanins in the two interspeci c hybrids (Figure 6). A recent study showed that high DFR expression levels lead to the production of colored anthocyanins in the Mitchell line of Petunia [32]. Similar ndings were reported for Litchi chinensis Sonn [40] and Malus hupehensis [41].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the present study, the expression levels of genes encoding DFR (LOC101293459 and LOC101293749) were higher in BF1 and BF2 than in FN, resulting in the accumulation of anthocyanins in the two interspeci c hybrids (Figure 6). A recent study showed that high DFR expression levels lead to the production of colored anthocyanins in the Mitchell line of Petunia [32]. Similar ndings were reported for Litchi chinensis Sonn [40] and Malus hupehensis [41].…”
Section: Discussionsupporting
confidence: 75%
“…The results showed that 17 DAMs (primarily pelargonidin and peonidin derivatives) were co-up-regulated (Table 2). Inconsistent with the ndings of previous studies, the abundance of cyanidin derivatives, which produce a magenta fruit skin, was co-down-regulated, indicating that cyanidin derivatives may be lost during the fruit color formation of the FN interspeci c hybrids [32]. In addition, red is closely related to the accumulation of anthocyanins in maturing fruits [33] and the anthocyanin concentration is an important index for examining fruit colors.…”
Section: Discussionsupporting
confidence: 71%
“…The results showed that 17 DAMs (primarily pelargonidin and peonidin derivatives) were co-up-regulated (Table 2 ). Inconsistent with the findings of previous studies, the abundance of cyanidin derivatives, which produce a magenta fruit skin, was co-down-regulated, indicating that cyanidin derivatives may be lost during the fruit color formation of the FN interspecific hybrids [ 32 ].…”
Section: Discussionsupporting
confidence: 70%
“…6 ). A recent study showed that high DFR expression levels lead to the production of colored anthocyanins in the Mitchell line of Petunia [ 32 ]. Similar findings were reported for Litchi chinensis Sonn [ 40 ] and Malus hupehensis [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, only limited regulators have been experimentally verified to be involved in the regulation of carotenoid metabolism in algae. For further study, by referring to relevant studies in plants through homology of regulatory factors, muti-omics integration analysis of metabolomics and transcriptomics, and molecular biology techniques, ,,, much more regulators and regulation networks can be discovered in algae. Among them, comparative transcriptome sequencing can be an important means to explore potential regulatory factors according to the correlation of gene expression and carotenoid contents …”
Section: Future Challenges and Prospectsmentioning
confidence: 99%